IMPROVING COAL-WATER FUEL PREPARATION TECHNOLOGY (Transport systems and technologies, 2018)
The proposed coal-water fuel production technology, based on the coal slurry, allows revive and conserve natural resources and ensure use non-liquid fuel feedstock in fueland energy complex of Ukraine. The analysis different ways crushing of coal in single cycle coal-water fuel production allowed us to determine least energy-intensive technologythis fuel. Summary processes preparation of coal-water fuel is coal grinding particles enriched oil agglomeration method, simultaneously with mixing them with water and reagent, aplasticizer in ball mill. Prepared coal sludge process are single-stage wet grinding in laboratory ball mill in presence of reagent-plasticizer. It was found that milling of largeclasses coal are continuously contents middle classes in initial period grinding is increased, and by the end grinding is markedly reduced. The content fine fractions ingrinding process constantly increased. Consequently, speed of grinding is significantly affected by initial coal particle size. In an industrial environment are most effective wetgrinding mill drum, such as rod and ball mills. Use as stabilizer humic preparation (sodium humate) gives stable suspension with substantially no time-changing rheologicalcharacteristics. The article describes technology of preparation coal-water slurry of coal sludge Donets Basin, and provides method for improving properties coal-water slurries.Object of the study – coal-water slurry of coal sludge Donets Basin. Purpose of the study – improvement technology for preparation of coal-water slurry through use effectivemethods grinding coal slurry and improve the properties coal-water slurries. Method of the study – comparison, analysis and synthesis, synthesis, formalization, systematicapproach. The results can be used by scientific, engineering and management professionals involved in technology research and preparation of coal-water fuel combustion in boilerplants various enterprises in Ukraine. Forecast assumptions about the object of study – search for optimal preparation technology of coal-water slurries having desired propertiesuse in power systems businesses.a
Keywords: fuel, preparation, coal slurry, grinding, stability, properties, agglomeration